Interaction of Axonal Chondrolectin with Collagen XIXa1 Is Necessary for Precise Neuromuscular Junction Formation - Oprisoreanu, Ana-Maria; Smith, Hannah L.; Arya, Sukrat; Webster, Richard; Zhong, Zhen; Wehner, Daniel; Cardozo, Marcos J.; Becker, Thomas; Talbot, Kevin; Becker, Catherina G. (Cell Reports, 2019)
The C-type lectin-domain-containing transmembrane molecule Chondrolectin (Chodl) is expressed by motor neurons. Oprişoreanu et al. show that binding of axonal Chodl to extracellular collagen XIXa1 is needed for proper neuromuscular junction differentiation in mice and zebrafish, as well as axon extension and branching at synapses in zebrafish.
CRIS-Team Scopus Importer:2022-08-03
Keywords: axon growth; CaP motor neurons; extracellular matrix; horizontal myoseptum; muscle pioneer cells; neuromuscular junction; stalled motor axons; synapse; zebrafish